Molecular phylogeny and systematics of Acrotoma (Gastropoda: Clausiliidae) from the Caucasus. Issue 7 (3rd October 2018) - Hausdorf, Bernhard; Walther, Frank; Neiber, Marco T.
Abstract : The land snail genus Acrotoma (Clausiliidae) from the western Greater Caucasus is revised and a molecular phylogenetic analysis of the genus is presented. Shells and, as far as known, genitalia of 13 species are described and figured. Two species are described as new to science, i.e., A . vespa sp. nov. and A . enguriensis sp. nov. The diagnostic characteristics are summarized in a table. All locality records are listed and shown in distribution maps. Based on Bayesian, Maximum likelihood and Maximum parsimony analyses of mitochondrial and nuclear DNA sequences we revise the classification of the genus and suggest a division into three subgenera, Iliamneme, Acrotomina and Acrotoma s. str. The radiation of the Acrotoma species in the Pliocene and Quaternary might have been triggered by the orogenesis of the Greater Caucasus, which created habitats, such as canyons and alpine environments, to which the Acrotoma species adapted.www.zoobank.org/urn:lsid:zoobank.org:pub:6B14BE68-0E07-42EF-B08D-A75B2138B72F